Efektivitas Game-Based Learning Dalam Meningkatkan Kemampuan Berfikir Kreatif Matematis Siswa: Literatur Review - Suci Rahma Sari; Hasanuddin Hasanuddin (CV. Lentera Literasi Indonesia, 2026)
The purpose of this study is to evaluate the effectiveness of game-based learning in mathematics education in improving students’ creative thinking skills. This study addresses this objective through a literature review. The background of the study highlights the importance of developing students’ creative thinking skills in mathematics to meet the demands of the 21st century. The method employed is a literature review of studies published between 2021 and 2026, including journal articles and academic books. The analysis consists of identification, classification, evaluation, and synthesis. The findings indicate that game-based learning is effective in improving students’ mathematical creative thinking skills. Learning through games not only increases students’ motivation to learn but also creates an enjoyable learning environment. This approach can also encourage students to think more intelligently, creatively, and deeply when dealing with problems. Furthermore, it encourages students to participate more actively in developing new strategies and communicating their ideas. Therefore, game-based learning is highly suitable as an alternative instructional approach for enhancing students’ mathematical creativity.